Behaviour disorders in children with an intellectual disability - Ageranioti-Bélanger, Stacey (Pulsus Group Inc, 2012)
Behaviour disorders are frequent in children with an intellectual disability, regardless of the underlying etiology. They are often disabling, and can create problems in everyday life and can mask, or reveal, an organic or psychiatric illness. Such behaviours are often chronic and more than one may be present in the same individual. This is further complicated by the fact that parents often do not seek help for the problem, perhaps believing that it is due to the child’s disability and cannot be treated. The present review describes some general concepts dealing with the management of behaviour disorders commonly seen in children and youth with an intellectual disability, and gives a high level overview of behaviours commonly problematic in this patient population including sleep disturbances, agitated and aggressive behaviours, and self-injury behaviour. In general, while pharmacological treatment is possible, behavioural intervention is a more effective and better tolerated form of treatment.